CHARACTERISTICS OF THE ADVISORY PROCESS IN THE WORK WITH SELECTED FARMS IN VOJVODINA - Janković, Dejan; Petrović, Živojin; Čikić, Jovana (Economics of Agriculture, 2010)
In the paper authors analyse some of the characteristics of the advisory process on the selected farms in Vojvodina. By emphasising the extension as a process, authors wish to underline the necessity of proper understanding of complex social relations that surround and cause such processes and, within which, these relations are generated, as well. Authors analysis stands within the theoretical-hypothetical frame of the recent contributions of the extension science. Analysed data stem from the systematic notes of agricultural advisors of the Agricultural Extension Service of Vojvodina that, in a pretty clear way, represent a live reflexion of their work and everyday relations with farmers/selected farms in Vojvodina.